Application of the reflective cracking phenomenon in the pavement overlay design - Pais, Jorge C. (2001)
An asphalt concrete overlay layer placed above a cracked layer is subjected to four primary distress mechanisms due to traffic loads: tensile strain at the bottom of the overlay; tensile strain at bottom of the existing surface course; compressive strain at the top of the unbound layers, and reflective cracking. Existing overlay design methods usually only take into account the first three of these primary distress mechanisms. In these cases, the propagation of existing cracks through the new overlay is not directly considered. This paper presents a design method that directly includes a criterion for the fourth pavement distress mechanism — reflective cracking. The development of this new design method is based on the estimation of the crack activity after overlay, using a 3D finite element model. This crack activity after overlay is used to perform laboratory reflective cracking test where this crack activity is applied and the reflective cracking fatigue life is obtained.